New tools for collaboration : the experience of the U.S. intelligence community - Treverton, Gregory F. (CSIS report., 2016)
"The Intelligence Community does not lag far behind the private sector in using collaborative tools; indeed, it has developed an impressive array. However, the most used tools, like instant messaging (IM), are employed primarily within agencies for peer-to-peer communication and hence are neither widely collaborative nor especially novel: they are different ways of accomplishing familiar functions. The array of collaborative tools across agencies -- ranging from IM to blogs to a wiki called Intellipedia -- is impressive but used mostly by enthusiasts. This report identifies lessons learned from looking at the use of internal collaborative tools across the Intelligence Community, especially across the four biggest agencies: Central Intelligence Agency, Defense Intelligence Agency, National Security Agency, and National Geospatial Intelligence Agency"--Publisher's web site